Relationship of glycemic variability with delirium and mortality among critically ill elderly patients with sepsis: A retrospective matched cohort study - Jianqin Huang; Jiexuan Xu; Yu Zhai; Shuting Liu; Pengcheng Duan; Jiayan Liang; Yile Tian; Murong Lu; Xuemei Liu; Hongjing Yu (PLoS ONE, 2026)
Objective The associations of glycemic variability (GV) with the occurrence of delirium and 90-day and 180-day mortality in critically ill patients with sepsis remain unclear. This study aimed to investigate the associations of glycemic variability with the development of delirium and death. Method This study employed a retrospective analysis of elderly sepsis patients admitted to the intensive care unit (ICU) for the first time. Patients were categorized into two groups based on their GV: a high-risk group (< 21.399%) and a low-risk group (≥21.39%). The relationship between GV and delirium was assessed via logistic regression and restricted cubic splines. Cox regression was employed to analyze the relationship between GV and patients’ 90-day and 180-day mortality. Results This study included 12228 elderly patients who were diagnosed with sepsis. The high-risk group presented a significantly elevated risk of delirium (27.9% vs 22.1%) and higher 90-day (40.0% vs 30.1%) and 180-day (46.0% vs 35.7%) mortality rates (all p < 0.001). The increase in GV was approximately nonlinear with increasing risk of delirium. In addition, high GV was associated with the greatest risk among delirium (OR = 1.122, 95% CI 1.023–1.230), 90-day mortality (HR = 1.149, 95% CI 1.07–1.227) and 180-day mortality (HR = 1.153, 95% CI 1.085–1.224) in elderly sepsis patients. Conclusion GV is independently associated increased risk of delirium and 90-day and 180-day mortality in elderly sepsis patients, indicating that GV can serve as a biomarker for identifying at higher risk of delirium and mortality in sepsis patients.